Contribution Of Body Body Towards Basket Under Skills In Basketball Extracurricular Private Vocational School 01 Arga Makmur - Rian Arindi Pradinata; Mesterjon Mesterjon; Feby Elra Perdima (Perkumpulan Dosen Muda Bengkulu, 2021)
This study aims to determine the contribution of body flexibility to under basketball skills. The formulation of the problem in this study is whether there is a relationship between body flexibility and under basketball skills in basketball extracurricular activities at SMPN 01 Arga Makmur? and how big the contribution of body flexibility to under basketball skills in basketball extracurricular activities at SMPN 01 Arga Makmur? This research was conducted at SMP Negri 01 Argamakmur in 2020. The research method used is the correlation method with the statistical product moment, this research is objectively or as is with a sample of 24 basketball players taken by total sampling technique. The results of body flexibility data on under basketball skills r count = 0.97 r table = 0.361 then Ho is rejected and Ha is accepted. This means that there is a significant relationship between X and Y. The contribution of body flexibility to under basketball skills is K = r2 x 100% = 0.97% x 100%, namely 94.09%. So it can be concluded that there is a strong relationship.